Scoulerine promotes cytotoxicity and attenuates stemness in ovarian cancer by targeting PI3K/AKT/mTOR axis - Wang Fang; Zhang Yang; Pang Rui; Shi Shaohong; Wang Ran (Acta Pharmaceutica)
In women, ovarian cancer is a common gynecological cancer associated with poor prognosis, reoccurrence and chemoresistance. Scoulerine, a benzylisoquinoline alkaloid, has been reported effective against several carcinomas. Thus, we investigated the impact of scoulerine on ovarian cancer cells (OVCAR3). Cell viability was assessed by MTT assay, migration was determined by Boyden Chamber assay, while the invasion was monitored by Boyden Chamber assay using the matrigel. The stemness properties of OVCAR3 cells were observed by tumorsphere assay. Epithelial to mesenchymal transition (EMT) and stemness-related protein markers were monitored by real-time PCR analysis and immunoblotting. Scoulerine inhibits the viability of OVCAR3 cells with the IC50 observed at 10 µmol L–1 after 48 h treatment. Scoulerine inhibited the colony-forming ability, migration and invasiveness of OVCAR3 cells in a dose-dependent fashion. Scoulerine treatment also drastically reduced the spheroid-forming ability of OVCAR3 cells. The mesenchymal and stemness--related markers like N-cadherin, vimentin, CD-44, Oct-4, Sox-2 and Aldh1A1 were downregulated, whereas the epithelial markers like E-cadherin and CD-24 were upregulated in scoulerine-treated cells. The upstream PI3K/Akt/mTOR-axis was downregulated in scoulerine-treated cells. We concluded that scoulerine successfully perturbs the cancerous properties of OVCAR3 cells by targeting the PI3K/Akt/mTOR axis. In vivo studies revealed a substantial decrease in tumor mass and volume after scoulerine treatment. Furthermore, scoulerine treatment was found to decrease oxidative stress factors in ovarian cancer mice model. Scoulerine is a potential anticancer agent against ovarian cancer and can be considered as a lead molecule for this malignancy, provided further investigations are performed.